Information technologies in the work of the manager of an industrial enterprise - Kobіelіev, I. V. (Teadmus OÜ, Tallinn, 2025)
The report substantiates that the development of information technologies has become a determining factor in the successful operation of industrial enterprises in the XXI century. The use of modern digital solutions allows to significantly increase the efficiency of management, optimize production processes and improve coordination between structural units. operating costs and the ability to flexibly respond to market challenges.
Keywords: information technology; digitalization; implementation; use; industrial enterprises; efficiency